2020
DOI: 10.3390/foods9101343
|View full text |Cite
|
Sign up to set email alerts
|

Bud-Derivatives, a Novel Source of Polyphenols and How Different Extraction Processes Affect Their Composition

Abstract: The use of herbal food supplements, as a concentrate form of vegetable extracts, increased so much over the past years to count them among the relevant sources of dietetic polyphenols. Bud-derivatives are a category of botanicals perceived as a “new entry” in this sector since they are still poorly studied. Due to the lack of a manufacturing process specification, very different products can be found on the market in terms of their polyphenolic profile depending on the experimental conditions of manufacturing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 57 publications
7
29
0
1
Order By: Relevance
“…The most common methods used for the extraction of bioactive compounds from vegetal matrixes (plants, vegetables, fruits, and by-products), are maceration, Soxhlet [ 1 , 2 ], and conventional solid-liquid extraction [ 10 ], although shaking and heated reflux have also been used [ 1 , 10 ]. Other methods as microwave, microwave-assisted [ 11 , 12 , 13 , 14 ], ultrasound-assisted [ 1 , 2 , 14 , 15 , 16 , 17 , 18 ], and super-critical fluid extraction [ 1 , 2 , 14 , 18 ] have been used to increase extraction yield [ 2 ]. The efficiency of the extraction depends on several factors such as temperature, sample (the type of plant and pre-conditioning), time, and the solvent agent, among others.…”
Section: Introductionmentioning
confidence: 99%
“…The most common methods used for the extraction of bioactive compounds from vegetal matrixes (plants, vegetables, fruits, and by-products), are maceration, Soxhlet [ 1 , 2 ], and conventional solid-liquid extraction [ 10 ], although shaking and heated reflux have also been used [ 1 , 10 ]. Other methods as microwave, microwave-assisted [ 11 , 12 , 13 , 14 ], ultrasound-assisted [ 1 , 2 , 14 , 15 , 16 , 17 , 18 ], and super-critical fluid extraction [ 1 , 2 , 14 , 18 ] have been used to increase extraction yield [ 2 ]. The efficiency of the extraction depends on several factors such as temperature, sample (the type of plant and pre-conditioning), time, and the solvent agent, among others.…”
Section: Introductionmentioning
confidence: 99%
“…However, these products are still poorly studied, even if some in vitro/in vivo studies for veterinary and human use have been already reported [1][2][3]. Moreover, the high number of herbal products on the botanical market and an almost absence of specific legislation to control their quality and safety causes many issues on these products (e.g., adulteration, falsification, and fraud) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, binding to proteins may affect the absorption of polyphenol compounds and reduces their bioavailability and nutritional benefits [ 12 ]. Factors such as the structures of polyphenols and proteins and the ratio of polyphenol/protein can affect the mode of interaction between proteins and polyphenols [ 13 ]. The interaction between polyphenols and several enzymes such as tyrosinase, amylase, xanthine oxidase, and peroxidase has been reported [ 14 ].…”
Section: Introductionmentioning
confidence: 99%